2013
DOI: 10.4236/cweee.2013.22005
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study for Power Generation during Peak Hours with a Hybrid System in a Recycled Paper Mill

Abstract: The differential pricing for peak hours encourages industrial consumers to look for independent power supplies for the period from 19 to 22 hours. This paper presents a study to identify the optimal solution for a recycled paper mill that also intends to work in that period. The factory is located in Rio Grande do Sul, in southern Brazil, and considers the use of a diesel gen set, a micro hydro power plant and possibly PV modules. Two micro hydro power plants were considered in the study, an old plant to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The rural electrification agency (REA) has classified Nigeria as one of the potential areas where off-grid hybrid renewable energy can be used effectively for rural electrification [8,9]. Off-grid rural populace deserves sustainable, reliable and cost-effective energy system to serve as an alternative to the environmentally unfriendly and expensive power supplied by the conventional energy system [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rural electrification agency (REA) has classified Nigeria as one of the potential areas where off-grid hybrid renewable energy can be used effectively for rural electrification [8,9]. Off-grid rural populace deserves sustainable, reliable and cost-effective energy system to serve as an alternative to the environmentally unfriendly and expensive power supplied by the conventional energy system [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that the hybrid system is efficient in emission reduction. A study to identify the best solution for a recycled paper mill located in Rio Grande do soul, Southern Brazil for peak hours (19-22 hours) was conducted by [11]. The method considered the cost at peak hours only, the reliability was not considered.…”
Section: Introductionmentioning
confidence: 99%
“…Among the other case studies, the first three of them (Silva, Cardoso & Beluco, 2012;Beluco & Ponticelli, 2014;Beluco et al, 2013) deal with the insertion of PV modules and-or other components or new fuels into previously existing diesel hybrid systems and the fourth (Benevit et al, 2016) of them studies the subtle influence of different wind energy availability profiles on the performance of a wind diesel hybrid system.…”
Section: Introductionmentioning
confidence: 99%
“…15 Water availability for the two alternatives of the case study presented byBeluco et al (2013a). 16 Solar availability for the case study presented byBeluco et al (2013a).…”
mentioning
confidence: 99%